Severe osteopathia striata with cranial sclerosis in a female case with whole WTX gene deletion12. Issue 3 (7th February 2013) - Herman, Sean B.; Holman, Sarah K.; Robertson, Stephen P.; Davidson, Lynn; Taragin, Benjamin; Samanich, Joy
Abstract Osteopathia striata with cranial sclerosis (OSCS) is caused by truncating mutations or deletions in the X linked gene, WTX, and is characterized by sclerotic striations of the metaphyses and diaphyses of long bones, pelvis, and scapula, along with craniofacial hyperostosis. Females typically manifest with craniofacial dysmorphisms including macrocephaly, hypertelorism, depressed nasal bridge, and hypoplastic maxilla, often have cleft palate, and less often extra skeletal anomalies. Here we report on a sporadic female patient with OSCS born at 33 weeks, with coarse facies, an abnormal head shape, cleft palate, pyloric stenosis, a small VSD, and laryngotracheomalacia sufficiently severe to require tracheostomy placement. Characteristic radiologic findings were apparent on skeletal survey and cranial CT. At age 5, she showed mild delays in neurodevelopmental milestones. A deletion of WTX and the adjacent gene ASB12 was detected via MLPA and there was no skewing of the X‐chromosome inactivation pattern (58:42). Neurodevelopmental delays can manifest in females with OSCS and deletions at the WTX locus, but deletion of the ASB12 gene in this case suggests it is unlikely to contribute to the pathogenesis of this complication. Implication of ASB12 in the patient's other unique features such as laryngotracheomalacia and pyloric stenosis is also unlikely. This case illustrates an early presentation of severe OSCS in a female without skewing of the X‐chromosome inactivation pattern, emphasizing the variable expressivity of this disorder. © 2013 Wiley Periodicals, Inc.